The Influence of Product Quality and Promotion on Tofu Sales Decisions in Dalu 10B Village MSMEs - Sihite, A.M Hatuaon; Lubis, Ikwan; Sianturi, Maringan; Lubis , Nurin Natiqoh (Journal of Economics, Management and Accounting (JEMA), 2023)
Dalu 10B Village is the name of an area in Tanjung Morawa District, Deli Serdang Regency. The residents of Dalu Sepuluh B village consist of various tribes such as Javanese, Malay, Batak, Mandailing, Javanese, Banten and also other tribes. The religions are also different such as Islam, Hinduism, and Christianity. The majority of the residents of Dalu Sepuluh B are Muslims. In Hamlets I, II, III, IV, V, VI, VII, VIII, IX and X in Dalu Sepuluh B, the majority of the population is Javanese, namely the indigenous tribe of Dalu Sepuluh B Village. In Law Number 6 of 2014 concerning Villages, it is stated that a village is a legal unit that has territorial boundaries that have the authority to regulate and manage government affairs, the interests of the local community based on community initiatives, rights of origin and/or traditional rights that are recognized and respected in the government system of the Unitary State of the Republic of Indonesia. Product quality is the ability of a product to carry out its functions including, durability, reliability, accuracy, ease of operation and repair, and other valuable attributes. Marwanto (2015) in (Cardia et al., 2019) states that product quality is the overall characteristics and properties of goods and services that affect the ability to meet stated and implied needs and desires. Promotion is a variable in the marketing mix that is important for companies to carry out in marketing their products or services. Promotion is a one-way flow of information or persuasion created to direct a person or organization to an action that creates an exchange in marketing. Promotional factors can influence consumer behavior and thinking in making buying decisions. With promotion, it can change a person's mind from being previously not interested in a product to being interested in a product and trying the product so that consumers make a purchase. Based on the results of the research that has been carried out, product quality has a very significant effect on increasing the sales of Tofu products in Dalu 10B Village because quality can determine the increase in consumer satisfaction. Promotions also need to be considered and carried out, whether it is using Facebook, Instagram WA and others to increase sales to run the alignment of product quality so that it causes an increase in consumer customers. Quality and promotion must be carried out simultaneously for the sake of increasing sales because it is not done only one of them. Because both are very influential in increasing sales, both promotions that can cause an increase in consumers and quality that affects consumer satisfaction significantly.